2020
DOI: 10.1055/s-0040-1701663
|View full text |Cite
|
Sign up to set email alerts
|

Transversus Abdominis Plane Blocks in Microsurgical Breast Reconstruction: A Systematic Review and Meta-analysis

Abstract: Background Transversus abdominis plane (TAP) blocks have been shown to significantly reduce pain and narcotic consumption following major abdominal surgeries. This study investigates the literature on their use in microsurgical breast reconstruction. Patients and Methods A systematic review of TAP blocks in autologous breast reconstruction was performed. Results Across 10 included studies, 174 patients (5 studies) received an intraoperative TAP block injection, 185 patients (4 studies) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Time to perform transversus abdominus plane blocks is minimal, having been reported to range between 5 and 24 minutes and causing no significant delays. 22–24 Greater analgesic benefits were observed in unilateral immediate reconstruction relative to delayed unilateral or bilateral reconstructions and in patients with body mass indexes of more than 25 kg/m 2 . 25,26 Of note, the majority of flaps assessed in the present analysis were muscle-sparing, including deep inferior epigastric perforator, superficial inferior epigastric artery, and muscle-sparing transverse rectus abdominus myocutaneous flaps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time to perform transversus abdominus plane blocks is minimal, having been reported to range between 5 and 24 minutes and causing no significant delays. 22–24 Greater analgesic benefits were observed in unilateral immediate reconstruction relative to delayed unilateral or bilateral reconstructions and in patients with body mass indexes of more than 25 kg/m 2 . 25,26 Of note, the majority of flaps assessed in the present analysis were muscle-sparing, including deep inferior epigastric perforator, superficial inferior epigastric artery, and muscle-sparing transverse rectus abdominus myocutaneous flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Both this study and previous meta-analyses demonstrate significant reductions in postoperative pain, opioid consumption, and duration of hospitalization associated with transversus abdominus plane block use. 11,22 The majority of transversus abdominus plane blocks were performed by plastic surgeons under ultrasound guidance, with no complications observed. Time to perform transversus 8e Plastic and Reconstructive Surgery • July 2022 abdominus plane blocks is minimal, having been reported to range between 5 and 24 minutes and causing no significant delays.…”
Section: Transversus Abdominus Plane Blocksmentioning
confidence: 99%
“…We found that TAP blocks did not have an appreciable effect on either postoperative narcotic prescriptions or conversion to prolonged opioid use. A systemic review by Abdou et al of single-center studies on patients undergoing abdominally based microsurgical breast reconstruction indicated a statistically significant reduction in total opioid consumption with the use of a TAP block in the inpatient setting; however, other studies have indicated no significant reduction [ 17 , 20 ]. Moreover, there is scarce data in the literature on the long-term impact of TAP blocks on opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients undergoing DIEP flap breast reconstruction, a bupivacaine TAP blockade was associated with significantly reduced narcotic consumption compared with infusion pump anesthetic administration and local anesthetic injection (11). Recently, liposomal bupivacaine, which has a long duration of effect, has been widely used in TAP blocks (12). The TAP block technique using liposomal bupivacaine has also been reported to reduce the length of hospital stay after surgery and costs associated with postoperative management after breast reconstruction surgery (8).…”
Section: Discussionmentioning
confidence: 99%